Possibility of Applying Business Process Management Methodology in Logistic Processes Optimization - Božić, Diana; Stanković, Ratko; Rogić, Kristijan (Promet - Traffic&Transportation, 2014)
Raising the service level and developing new logistic services require better understanding of logistic processes and possibilities of optimization. Different methodologies have been used for that purpose, while the application of Business Process Management (BPM) methodology is outlined in this paper. Identifying parts of logistic processes that could be optimized is facilitated by applying BPM methodology. It also enables more accurate quantification of impacts of the changes introduced in a particular process or activity on the processes as a whole and to other interacting processes. The application of BPM methodology is demonstrated in the case study, where a solution for logistic processes optimization is suggested and the prospective outcomes are simulated. The results of the logistic process comparative analysis have indicated a synergic effect of different improvements in sub-process on the effectiveness of the process as a whole, both on the operative and managerial level. The respective changes in workload distribution among interacting logistic processes have been quantified according to the same methodology.